Chemical Vapor Deposition for Advanced Polymer Electrolyte Fuel Cell Membranes. Issue 8 (14th February 2022) - Bellomo, Nicolas; Michel, Marc; Pistillo, Bianca Rita; White, Robin J.; Barborini, Emanuele; Lenoble, Damien
Abstract: Fuel cells will play a critical role in a renewable energy powered society, whether in mobility or stationary applications. Certain challenges remain to be addressed if performance and cost dynamics of these systems is to achieve large scale, high unit number roll out. This review deals with polymer electrolyte membrane‐based fuel cells with a specific focus on membrane materials and their innovative fabrication based on chemical vapor deposition (CVD) approaches. These deposition techniques are introduced, as are the potential improvements relating to cell performance, namely proton conductivity and stability. The potential benefits of applying CVD‐based synthesis in the fabrication of polymer electrolytes is also discussed with respect to future fuel cell development. Abstract : CVD technique for improved membrane performance : In the emerging renewable energy and hydrogen‐based economy of the future, proton exchange membranes (PEM) will be a key functional component in the development and (large scale) deployment of PEM‐based electrochemical cells. In this respect, this review discusses the use of innovative chemical vapor deposition (CVD) approaches to synthesis such polymeric membranes in the context of key performance criteria (e. g. conductivity and stability) for PEM fuel cells.